The Dynamics of Sine-Gordon System with Dirichlet Boundary Condition (Journal of Partial Differential Equations, 2000)
We prove the existence of the global attractor of Sine-Gordon system with Dirichlet boundary condition and show the attractor is the unique steady state when the damping constant and the diffusion constant are sufficiently large.
Keywords: Global attractor; gradient system; steady states